TC21/RRas2 regulates glycoprotein VI–FcRγ‐mediated platelet activation and thrombus stability. (4th July 2018) - Janapati, S.; Wurtzel, J.; Dangelmaier, C.; Manne, B. K.; Bhavanasi, D.; Kostyak, J. C.; Kim, S.; Holinstat, M.; Kunapuli, S. P.; Goldfinger, L. E.
Abstract : Essentials RAS proteins are expressed in platelets but their functions are largely uncharacterized. TC21/RRas2 is required for glycoprotein VI‐induced platelet responses and for thrombus stability in vivo . TC21 regulates platelet aggregation by control of αIIb β3 integrin activation, via crosstalk with Rap1b. This is the first indication of functional importance of a proto‐oncogenic RAS protein in platelets. Summary: Background: Many RAS family small GTPases are expressed in platelets, including RAC, RHOA, RAP, and HRAS/NRAS/RRAS1, but most of their signaling and cellular functions remain poorly understood. Like RRAS1, TC21/RRAS2 reverses HRAS‐induced suppression of integrin activation in CHO cells. However, a role for TC21 in platelets has not been explored. Objectives: To determine TC21 expression in platelets, TC21 activation in response to platelet agonists, and roles of TC21 in platelet function in in vitro and in vivo thrombosis. Results: We demonstrate that TC21 is expressed in human and murine platelets, and is activated in response to agonists for the glycoprotein (GP) VI–FcRγ immunoreceptor tyrosine‐based activation motif (ITAM)‐containing collagen receptor, in an Src‐dependent manner. GPVI‐induced platelet aggregation, integrin αII b β3 activation, and α‐granule and dense granule secretion, as well as phosphorylation of Syk, phospholipase Cγ2, AKT, and extracellular signal‐regulated kinase, were inhibited in TC21‐deficient platelets ex vivo . In contrast, these responses were normal in TC21‐deficient platelets following stimulation with P2Y, protease‐activated receptor 4 and C‐type lectin receptor 2 receptor agonists, indicating that the function of TC21 in platelets is GPVI–FcRγ‐ITAM‐specific. TC21 was required for GPVI‐induced activation of Rap1b. TC21‐deficient mice did not show a significant delay in injury‐induced thrombosis as compared with wild‐type controls; however, thrombi were unstable. Hemostatic responses showed similar effects. Conclusions: TC21 is essential for GPVI–FcRγ‐mediated platelet activation and for thrombus stability in vivo via control of Rap1b and integrins.